The hundred-mile-an-hour dog - Strong, Jeremy (India: Puffin, 2007)
A young English boy describes his relationship with his father and the special adventure they share together.
Keywords: Dogs -- Training -- Juvenile fiction; Dogs -- Training; Children's humorous fiction